2022
DOI: 10.1155/2022/9499317
|View full text |Cite
|
Sign up to set email alerts
|

FCGR3A Is a Prognostic Biomarker and Correlated with Immune Infiltrates in Lower-Grade Glioma

Abstract: Low-grade gliomas (LGGs) are primary invasive brain tumors that grow slowly but are incurable and eventually develop into high malignant glioma. Fc fragment of IgG receptor IIIa (FCGR3A) gene polymorphism may correlate with some cancers’ treatment responses. However, the expression and prognosis value of FCGR3A and correlation with tumor-immune infiltrate in LGG remain unclear. FCGR3A mRNA expression in gastric cancer (GC) was examined using TIMER and GEPIA databases. Correlations between FCGR3A expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Sun et al (2016) found that boron-supplemented water administered in low doses (80 mg/L) can promote the proliferation of intestine cells and inhibit apoptosis, while high doses of boron (320 and 640 mg/L) can increase apoptosis in the intestine and thus stimulate compensatory cell proliferation [36]. Xu et al (2022) stated that drinking water with low and moderate boron concentrations (10-80 mg/L) enhances the microstructure, immunity, barrier function, antioxidant activity, and cell proliferation of the jejunum in rats, but high boron concentrations (480 and 640 mg/L) show negative effects [37]. These findings suggest that a suitable quantity of boron enhances intestinal immune function by stimulating cell proliferation, enhancing the microstructure of the barrier, and elevating antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al (2016) found that boron-supplemented water administered in low doses (80 mg/L) can promote the proliferation of intestine cells and inhibit apoptosis, while high doses of boron (320 and 640 mg/L) can increase apoptosis in the intestine and thus stimulate compensatory cell proliferation [36]. Xu et al (2022) stated that drinking water with low and moderate boron concentrations (10-80 mg/L) enhances the microstructure, immunity, barrier function, antioxidant activity, and cell proliferation of the jejunum in rats, but high boron concentrations (480 and 640 mg/L) show negative effects [37]. These findings suggest that a suitable quantity of boron enhances intestinal immune function by stimulating cell proliferation, enhancing the microstructure of the barrier, and elevating antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…FCGR3A, which functions as a receptor for the Fc region of immunoglobulin γ with low affinity, demonstrated upregulation in the NC vs. B10 comparison group [ 60 ]. Furthermore, it was identified as a predictive biomarker that was linked to tumor prognosis [ 60 , 61 ]. The interferon system contains the first two identified STAT proteins, which have a crucial function in regulating STAT-mediated signaling in host immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…FCGR3A (Fc fragment of IgG receptor IIIa), a transmembrane glycoprotein, is expressed on natural killer cells and inhibits the growth of liver tumor cells. FCGR3A gene is associated with the risk of lesions in several oncological diseases, for example, FCGR3A gene polymorphisms are positively associated with the risk of lesions in colorectal cancer, and genetic variants of FCGR3A are associated with drug resistance in rheumatoid arthritis ( 19 , 20 ). FCGR3A has been shown to be involved in multiple immune cell infiltration and DNA mismatch repair genes, while drug sensitivity analysis showed that higher FCGR3A expression predicted lower IC50 (half maximal inhibitory concentration) values for the majority of drugs ( 21 ), however, the prognostic value of FCGR3A expression in prostate tumors and its correlation with immune infiltration are unclear.…”
Section: Introductionmentioning
confidence: 99%